2012
DOI: 10.1503/cjs.032910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgeon fatigue on hip and knee arthroplasty

Abstract: Duration of surgery and incidence of intraoperative complications for THA may increase with later surgery start time; however, the relatively small statistical differences observed imply that they likely are not clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…It has been demonstrated that performing preoperative warm-up exercises for approximately 15 minutes with simple surgical tasks lead to a substantial increase in surgical skill pro ciency [12]. A few studies found that surgeon fatigue increased throughout the operative day, causing an increase in the time required to complete surgeries [9,[13][14]. A study by Willis-Owen et al suggested that a longer duration of surgery for TKA led to an increased infection rate [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that performing preoperative warm-up exercises for approximately 15 minutes with simple surgical tasks lead to a substantial increase in surgical skill pro ciency [12]. A few studies found that surgeon fatigue increased throughout the operative day, causing an increase in the time required to complete surgeries [9,[13][14]. A study by Willis-Owen et al suggested that a longer duration of surgery for TKA led to an increased infection rate [15].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a predigestion technique and improvements in implants, ve or more arthroplasty cases are planned in a single operating room each day in many large orthopaedics centres. To date, few studies have examined the in uence of surgical case order on the surgical complication rate or clinical outcome of total knee joint arthroplasty, and the results have been con icting [7][8][9]. In the current study, we retrospectively viewed our centre's experience to examine whether the case order in uenced the perioperative outcomes of TKA.…”
Section: Introductionmentioning
confidence: 99%
“…There is support in the literature that patient outcomes are adversely affected by time-of-day and fatigue in operator-dependent cognitive and technical tasks (11). Specifically laparoscopic procedures, cardiac interventions, and endotracheal intubations have been shown to have inferior outcomes when performed later in the day (6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, it is believed that operative duration depends on factors related to clinical issues or patients [1], e.g., age, gender, and body mass index. It is also found that operative duration is affected by the surgeon's operating skills [2,3], assistant surgeons [4,5] management policies [6], switching of teams [7], and surgeon fatigue [8]. Predictors of operative duration of general thoracic surgeries are identified in [9].…”
Section: Introductionmentioning
confidence: 99%